Psalm 30 read twice and understood two times - Loader, James A. (Old Testament Essays, 2003)
Psalm 30 is subjected to two readings, the first of which takes the psalm as an expression of the traditional form-critical genre of the individual song of thanksgiving. The second reading seeks to consider the same motifs within the same structural organisation of the poem under the impact of the caption. The heading, whether itself edited at a later time than its original insertion or not, enables the reading of the psalm as a collective instead of an individual thanksgiving prayer. It is suggested that this kind of redactional criticism is theologically significant, laying bare as it does what exegesis has been doing all along, even when it claimed to be objectively practising historical criticism. It is also suggested that such an approach may help to counter the primacy, if not the papacy, of the 'final text' as this seems to be accepted by conservative as well as progressive currents within the biblical disciplines.
free